Validation and new synonymies proposed for Cheiracanthium species from South and Southeast Asia (Araneae, Clubionidae) - Dankittipakul, Pakawin; Beccaloni, Janet (Zootaxa, 2012)
The primary types of Cheiracanthium species from South and Southeast Asia were examined. Cheiracanthium insigne O.P.–Cambridge, 1874 is considered a senior synonym of Eutittha gracilipes Thorell, 1895 (male). Eutittha truncata Thorell,1895 (female) is not a conspecific female of E. gracilipes, provisionally threated as a separate species and proposed hereas a valid taxon because it does not resemble the female of C. insigne. Cheiracanthium rupicolum (Thorell, 1897) is re-garded as a senior synonym of C. gyirongense Hu & Li, 1987. The Himalaya form of C. triviale (Thorell, 1895), whichwas mentioned and illustrated in Gravely (1931), was misidentified and belongs to C. rupicolum. Cheiracanthium insu-lanum (Thorell, 1878) bears strong resemblance to that of C. melanostomum (Thorell, 1895); they probably belong to the same species.